ANALISIS PELAKSANAAN STANDAR PROSES PEMBELAJARAN IPA BERBASIS KURIKULUM 2013 DI KELAS VIII SMP NEGERI PEKANBARU - Dini Yatul Fitri; Zuhelmi '; Syahril ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to find out the implementation of standard process at science learning based on Curriculum 2013 in Grade VIII of Junior High School of Pekanbaru according to students' perception in terms of four aspects: preliminary activities, core activities, closing and evaluation activities. The type of research used is survey research. The study population is the students of class VIII SMP Negeri 1, SMP Negeri 6 and SMP Negeri 23 Pekanbaru. Sampling using proportional random sampling technique. The research instrument used is a closed questionnaire. Based on the results of data analysis indicate that the implementation of a standard learning process based on Curriculum 2013 on preliminary activities obtained percentage 78.99%, the implementation of core activities with percentage of 79.43%, the implementation of cover activities with percentage of 75.22% and the implementation of evaluation activities with percentage of 79.03%. Overall, it can be concluded that the implementation of process standard according to students' perception on science lesson based on Curriculum 2013 in class VIII included in a good category with percentage 78,17%.Keywords: Process Standard, Science Lesson, Curriculum SMP 2013